Digestion and nitrogen conservation in cattle and buffaloes given rice straw with or without molasses - Abdullah, N.; Nolan, J. V.; Mahyuddin, M.; Jalaludin, S. (Cambridge University Press, 1992)
Using [ 14 C]urea, the rates of urea synthesis in the body, excretion in the urine and degradation in the rumen and gut were compared in 20-month-old Kedah-Kelantan cattle and swamp buffaloes at the Universiti Pertanian Malaysia, Malaysia in 1987. The animals were fed rice straw or straw plus molasses. The buffaloes were heavier than the cattle and had higher straw and nitrogen intakes, although these intakes did not differ significantly when compared on the basis of metabolic liveweight (W 0-75). Rumen pH in the buffaloes was lower, whereas ammonia and total volatile fatty acid (VFA) concentrations were higher than in the cattle. Total VFA concentration was lower when the diet contained molasses. Rumen bicarbonate kinetics did not differ significantly between species or diets. There were no significant differences between species in plasma urea concentration, or urea synthesis rate per W 0-75, or endogenous urea movement into the rumen per W 0-75. The buffaloes consumed more water and discharged twice as much urine as the cattle, but nevertheless excreted less urea per W 0-75, and a larger fraction of their endogenously produced urea entered the gut. Movement of urea into the rumen per W 0-75 was lower when the diet contained molasses.